PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR DI SMKN TAPANGO KABUPATEN POLEWALI MANDAR - Fidya Syamsul, Khusnul; Wahab, Abdul; Ahmad; Bunyamin, Andi; Mustamin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of the Discovery Learning learning model on student learning outcomes in the subject of Islamic Religious Education (PAI) for class XI at SMKN Tapango, Polewali Mandar Regency. This study uses a quantitative approach with an Ex Post Facto research type. The study population was all class XI students of SMKN Tapango, totaling 149 students, while the research sample was 60 students determined using the Slovin formula with a 10% error rate. Data collection techniques were carried out through questionnaires and documentation. The instrument validity test used Pearson Product Moment Correlation, while the reliability test used the Cronbach Alpha coefficient. Data analysis was carried out through descriptive statistical analysis, classical assumption tests, and multiple linear regression analysis with the help of the SPSS program. The results of the study indicate that the application of the Discovery Learning learning model is in the moderate category and student learning outcomes are also in the moderate category. The results of the partial test indicate that Free Discovery Learning and Guided Discovery Learning each have a positive and significant effect on student learning outcomes. In addition, the results of the simultaneous test (F test) showed a significance value <0.001, which means that both variables together have a significant effect on student learning outcomes. The results of the coefficient of determination (R²) test obtained a value of 0.916 or 91.6%, which indicates that the Discovery Learning learning model makes a very large contribution to improving student learning outcomes, while the remaining 8.4% is influenced by other factors outside the study. Thus, the Discovery Learning learning model is proven to be effective in improving student learning outcomes in the subject of Islamic Religious Education for class XI at SMKN Tapango, Polewali Mandar Regency.